PENERAPAN MEDIA PEMBELAJARAN BOARD SMART SONG (BSS) UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS X-9 DI SMA NEGERI 21 SURABAYA: PENELITIAN TINDAKAN KELAS - Riskiyah Kiki; Listyaningsih; Kristiwi Estuningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The purpose of this research is to increase students' interest in learning at SMAN 21 Surabaya by using the Board Smart Song (BSS) learning media. The type of research used is Classroom Action Research (PTK) with a Kemmis and Mc Taggart model design. The data collection technique used was observation of students, as well as a questionnaire about students' learning interest. The subjects of this research were in class X-9, totaling 34 people. The results of this research indicate that the application of the Board Smart Song (BSS) learning media can increase students' interest in learning in the Pancasila Education subject class X-9 at SMA Negeri 21 Surabaya. In cycle I there were 13 students in the medium category with a percentage of 38.23% and 21 students in the low category with a percentage of 61.76%. In cycle II there were 29 students in the very high category with a percentage of 85.29% and 5 students in the high category with a percentage of 14.71%. The conclusion of this research is learning using Board Smart Song (BSS) media. can increase students' interest in learning in the Pancasila Education subject class X-9 at SMAN 21 Surabaya